Allium cepa: A Natural Enhancer of Wound Closure and Cell Viability in O-Carboxymethyl Chitosan Films - Valencia-Gómez, Laura; Rodríguez-González, Claudia; Aguilar Valenzuela, Manuel; Miranda Cabrera, Faviola; Rodríguez López, Kenia; Hernández Paz, Juan; Reyes Blas, Hortensia; Sáenz Villela, Jesús; Olivas-Armendáriz, Imelda (Revista Mexicana de Ingenieria Biomedica, 2025)
Wound healing and cicatrization after tissue damage are essential for the body's recovery process. Regenerative medicine has been focused on finding biocompatible polymeric materials reinforced with natural active substances, which have healing, anti-inflammatory, and antimicrobial properties. This study aimed to enhance O-carboxymethyl chitosan films with Allium cepa extracts, endemic to Chihuahua, Mexico. The extract's properties were analyzed, and the results show the saponin, flavonoid, and terpenoid contents and an antioxidant activity of 70 %. Cicatrization in vitro was also studied, and the results show that a 15 mg/mL concentration of the Allium cepa extracts improved cellular proliferation and migration in fibroblasts, which was further confirmed in a cellular viability study of the O-carboxymethyl chitosan films loaded with 7 and 20 wt. % of the extract, which showed a higher percentage of cellular viability after three days. The study's results suggest that low extract concentrations can be used as an active ingredient in polymeric biomaterials to aid skin cicatrization.